Assessment of Attention Deficit Hyperactivity Disorder among Primary School Children From Teachers’ Perspective: A Cross-Sectional Study in Lebanon - Mhanna, Razan; Taha, Furat; Harakeh, Zeina; Awada, Sanaa; Assi, Roula Bou; Safa, Layal; Hatem, Georges (South Sulawesi Education Development, 2025)
Around 10% of Lebanese students exhibit learning disabilities at school, such as Attention Deficit Hyperactivity Disorder (ADHD). Teachers' assessments of ADHD symptoms support the early diagnosis of ADHD. This research aimed to evaluate ADHD prevalence and psychological symptoms among a convenience sample of students between 5 and 11 years, from their teachers’ perspective, and to assess factors associated with ADHD risk. A cross-sectional study was performed, involving a convenient sample of 130 students (average age: 8.7 years) attending grades 1 through 5 at a private school in Lebanon. The NICHQ Vanderbilt Assessment Scale, filled out by two teachers per student, was employed to evaluate ADHD symptoms. Additionally, a short survey was given to parents/caregivers to collect sociodemographic data. Analyses were performed at a significance level of 0.05 using SPSS version 29. Teachers' answers were largely consistent (p>0.05). French (36.2%) and Arabic (30.8%) were the main subjects taught by participating teachers. The prevalence of inattentive-type ADHD among students was 12%, while predominantly hyperactive and combined types were noted in 8.5% of students. Within the inattentive type, those aged 8-11 years (13.6%; p=0.034), males (15.8%; p=0.046), and first-grade students (21.4%; p=0.038) were significantly at higher risk. Higher risk for all ADHD types was also significantly associated with having divorced or separated parents, lower economic status, and parental unemployment. Moreover, being an only child was significantly linked to a greater risk of conduct disorder (18.8%; p=0.045). Teachers reported a considerable number of children with poor performance, namely in written expression, reading, and mathematics. Behavioral challenges in the classroom were also noted, including difficulty following directions (8%; p=0.707), disruptive behavior (8-9.3%; p=0.320), and troubles completing assignments (7-8%; p=0.740). These findings highlight a high prevalence of ADHD among school-aged children in Lebanese schools. Teachers play a crucial role in the early identification of inattentive and hyperactive symptoms, which is essential for preventing academic and behavioral difficulties at school.